Human Milk Blocks DC-SIGN–Pathogen Interaction via MUC1 - Koning, Nathalie; Kessen, Sabine F. M.; Van Der Voorn, J. Patrick; Appelmelk, Ben J.; Jeurink, Prescilla V.; Knippels, Leon M. J.; Garssen, Johan; Van Kooyk, Yvette (Frontiers in Immunology, 2015)
Beneficial effects of breastfeeding are well-recognized and include both immediate neonatal protection against pathogens, as well as long term protection against allergies and autoimmune diseases. Although several proteins have been identified to have anti-viral or anti-bacterial effects like secretory IgA or lactoferrin, the mechanisms of immune modulation are not fully understood. Recent studies identified important beneficial effects of glycans in human milk, such as those expressed in oligosaccharides or on glycoproteins. Glycans are recognized by the carbohydrate receptors C-type lectins on DC and specific tissue macrophages, which exert important functions in immune modulation and immune homeostasis. A well-characterized C-type lectin is DC-SIGN, which binds terminal fucose. The present study shows that in human milk, MUC1 is the major milk glycoprotein that binds to the lectin domain of DC-SIGN and prevents pathogen interaction through the presence of Lewis x-type oligosaccharides. Surprisingly, this was specific for human milk, as formula, bovine or camel milk did not show any presence of proteins that interacted with DC-SIGN. The expression of DC-SIGN is found in young infants along the entire gastro-intestinal tract. Our data thus suggest the importance of human milk glycoproteins for blocking pathogen interaction to DC in young children. Moreover, a potential benefit of human milk later in life in shaping the infants immune system through DC-SIGN cannot be ruled out.